The EcAMSat fluidic system to study antibiotic resistance in low earth orbit: Development and lessons learned from space flight. (August 2020) - Padgen, Michael R.; Chinn, Tori N.; Friedericks, Charlie R.; Lera, Matthew P.; Chin, Matthew; Parra, Macarena P.; Piccini, Matthew E.; Ricco, Antonio J.; Spremo, Stevan M.
Abstract: The E. coli AntiMicrobial Satellite ( EcAMSat ) was a successful spaceflight mission that performed an autonomous experiment to investigate the effects of microgravity on the antibiotic resistance of uropathogenic E. coli ; the latest in a series of biology-focused CubeSats developed at NASA Ames Research Center. While maintaining the bacteria at 37 °C, the payload delivered growth medium, different doses of the antibiotic gentamicin, and finally the metabolic indicator alamarBlue to each of 48 microwells in the fluidic card. An LED and detector system was used to monitor the changes in absorbance in each experiment well at three wavelengths (470, 525, and 615 nm), from which the growth of cells and their metabolic activity could be measured. The success of the mission was in part due to leveraging lessons learned and proven technologies from previous bio-CubeSat missions, including modified spare hardware from the PharmaSat payload. This paper details the design and assembly of the biofluidic system payload; the modifications to the PharmaSat hardware required to run the EcAMSat experiment and the challenges those changes created; and finally, the testing approach employed to ensure the success of the payload during the flight campaign. Highlights: EcAMSat : another successful NASA Ames bio-CubeSat spaceflight mission. Lessons learned from previous missions incorporated into fluidic design and testing. Vital to characterize and manage pressure in autonomous fluidic system. Systematic testing approach needed to select flight-worthy fluidic cards. Component and system-level biocompatibility testing ensured organism survival.